STUDY OF INHERITANCE NATURE OF MOTOR AND SPATIAL VISUALIZATOIN ABILITIES IN THE FAMILIES INHABITING IN VARIOUS REGIONS OF THE REPUBLIC OF ARMENIA (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
Evaluation of the role of genetic factors in the inheritance and the explanation of the inheritance patterns of above mentioned abilities become important connected with learning objectives. This paper refers the patterns of inheritance of motor and spatial visualization abilities. Test systems for the assessment of spatial visualization and motor abilities were studied by us attempting to figure out the patterns of inheritance of above mentioned abilities by implementation of spatial visualization and motor ability tests.
Keywords: spatial visualization abilities, motor abilities